Spontaneous recurrent episodes of wrist pain in a 16-year-old girl: a case of complex regional pain syndrome. (November 2016) - Gierthmühlen, Janne; Baron, Ralf; Blankenburg, Markus; Zernikow, Boris; Maier, Christoph
Abstract : Abstract: Introduction: Complex regional pain syndromes (CRPS) are disabling pain syndromes that can develop after minor tissue injury or trauma and are characterized by sensory, motor, and autonomic abnormalities distributed in a glove-like or stocking-like manner. Complex regional pain syndrome is well known in adults, but is relatively rare in children. Most of the reported cases of CRPS in children are clinical diagnoses that are not supported by examinations such as three-phase bone scintigraphy. Furthermore, different centres often use different diagnostic criteria for CRPS, which sometimes questions the diagnosis of CRPS. Objective/Methods: Although, recurrences and in particular relapses of CRPS have been observed, a periodically, nearly self-limiting course of disease without any residues in pain-free episodes and without any new obvious injury in CRPS is rather unusual. We present the case of a 16-year-old girl who reported recurrent spontaneous pain which lasted for 2 to 3 weeks and occurred approximately 2 times a year after the patient had experienced a mild trauma 3 years ago. Results: The pain was accompanied by swelling, temperature asymmetry, and decreased range of motion of the right hand without any complains in pain-free episodes. Recurrent symptoms occurred without any obvious trauma. Diagnosis of CRPS was made from clinical findings including quantitative sensory testing, increased periarticular radioisotope uptake in the delayed phase of three-phase bone scintigraphy and examination during anaesthesia. Multimodal inpatient pain treatment resolved her symptoms substantially. Conclusion: Complex regional pain syndrome in children may imitate rheumatologic diseases, and the course is different from adults despite similar clinical findings. Abstract : CRPS in children may imitate rheumatologic diseases, but should be considered if typical signs are present. Diagnosis can be supported by three-phase bone scintigraphy.